2009
DOI: 10.1007/s10750-009-9776-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of eutrophication in the eastern Gulf of Finland to nutrient load reduction scenarios

Abstract: The trophic status of the eastern Gulf of Finland, where the largest Baltic metropolis St. Petersburg sits at the mouth of the largest Baltic river Neva, is elevated but existing recommendations on water protection measures are controversial. In this study, the effects of nutrient load reductions on this ecosystem were estimated with the aid of a threedimensional coupled hydrodynamic-biogeochemical model. As a reference, the contemporary seasonal dynamics were simulated with nutrient inputs corresponding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…For example, Harima Nada is next to Osaka Bay and the Kii Channel, and nutrient transport from the Pacific Ocean is also well documented (Yanagi & Ishii, 2004). Sediment may also be a source of nutrients (Savchuk et al, 2009;Jikumaru et al, 2015;Nguyen & Maeda, 2016). In addition, seawater velocity may affect primary production by not only changing the retention of nutrients (Savchuk et al, 2009) but also light conditions (Wetsteyn & Kromkamp, 1994).…”
Section: Historical Changes In Primary Production and Loadings Of Land-originated Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Harima Nada is next to Osaka Bay and the Kii Channel, and nutrient transport from the Pacific Ocean is also well documented (Yanagi & Ishii, 2004). Sediment may also be a source of nutrients (Savchuk et al, 2009;Jikumaru et al, 2015;Nguyen & Maeda, 2016). In addition, seawater velocity may affect primary production by not only changing the retention of nutrients (Savchuk et al, 2009) but also light conditions (Wetsteyn & Kromkamp, 1994).…”
Section: Historical Changes In Primary Production and Loadings Of Land-originated Nutrientsmentioning
confidence: 99%
“…In fact, Yanagi & Ishii (2004) reported that the ratios of the landoriginated and ocean-originated nitrogen and phosphorus loadings to the Seto Inland Sea were 19:81 and 7:18, respectively, indicating that, while the contributions in each subarea may differ, nutrients originating from the open ocean are the main source for the entire Seto Inland Sea rather than land-originated nutrients. In addition, outer coastal areas may respond less sensitively to the reduction of land-originated nutrient loadings than inner coastal areas (Savchuk et al, 2009;Staehr et al, 2017). Therefore, questions about whether primary production has decreased in the Seto Inland Sea and how the reductions in the land-originated nutrient loads to the sea impact productivity remain unanswered.…”
Section: Introductionmentioning
confidence: 99%